2015
DOI: 10.1016/j.vetmic.2015.10.013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of PrP Sc accumulation on inflammatory gene expression within sheep peripheral lymphoid tissue

Abstract: HighlightsArrays quantified gene expression in peripheral LNs during sheep scrapie.Disease progression associated with alterations of inflammatory gene expression.Lymph node response contrasts with response of CNS.Step changes to gene expression after the detection of PrPSc in peripheral LNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Three of the genes within the highest homozygous H score on chromosome 7 (H = 0.85) were the MAP2K2 (Mitogen-Activated Protein Kinase Kinase 2) gene, the APBA3 gene (Amyloid Beta (A4) Precursor Protein-Binding, Family A, Member 3), and the ATCAY gene (Ataxia, cerebellar, Cayman type). These genes could be directly or indirectly involved in modulating scrapie or Yersinia Pseudotuberculosis, two widespread diseases of sheep and goat (Tanahashi and Tabira 1999;King and Turner 2004;Nordström et al 2005;Gossner and Hopkins 2015). It has been observed that Valdostana goats have a difference in several alleles of PRNP (Prion Protein gene: the major gene involved in scrapie) compared to the other breeds of northern Italy even if this difference was not significant (Colussi et al 2008).…”
mentioning
confidence: 99%
“…Three of the genes within the highest homozygous H score on chromosome 7 (H = 0.85) were the MAP2K2 (Mitogen-Activated Protein Kinase Kinase 2) gene, the APBA3 gene (Amyloid Beta (A4) Precursor Protein-Binding, Family A, Member 3), and the ATCAY gene (Ataxia, cerebellar, Cayman type). These genes could be directly or indirectly involved in modulating scrapie or Yersinia Pseudotuberculosis, two widespread diseases of sheep and goat (Tanahashi and Tabira 1999;King and Turner 2004;Nordström et al 2005;Gossner and Hopkins 2015). It has been observed that Valdostana goats have a difference in several alleles of PRNP (Prion Protein gene: the major gene involved in scrapie) compared to the other breeds of northern Italy even if this difference was not significant (Colussi et al 2008).…”
mentioning
confidence: 99%
“…2 , Supplementary Table 2 ). One significant SNP that was detected in our METAL-based analysis via Cochran’s Q -test for heterogeneity was intergenic between PLS3 and DACH2 ; with DACH2 previously implicated in the pathophysiology of scrapie ( Gossner and Hopkins 2015 ). However, it should also be noted that the same SNP implicating DACH2 was also among the top 39 ranked SNPs in a EMMAX GWAA ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…In human prion disease, inflammation-regulated expression of the micro RNA miR-146 was enhanced [65, 66]. In a puzzling contrast to the increased induction of inflammatory genes by PrPsc in the mouse brain, lymphoid tissues of sheep infected with PrPsc exhibit reduced expression of inflammatory genes [67]. Increased intracellular accumulation of Ca 2+ is present in the brain of CJD, and activation of the calpain-cathepsin axis occurs at the pre-clinical stage of the disease [68].…”
Section: Prpsc-induced Inflammation In Prion Diseasementioning
confidence: 99%